PERSEPSI DAN MINAT MAHASISWA TERHADAP PEMAHAMAN MATA KULIAH AKUNTANSI KEUANGAN (Studi Kasus Pada Mahasiswa Akuntansi Unisma) - Zakiyatun Nufus; Noor Shodiq Askandar; Abdul Wahid Mahsuni (Universitas Islam Malang, 2022)
This research was conducted with the aim of knowing the effect of students' perceptions and interests on understanding financial accounting courses. The population of this study were students majoring in accounting, Islamic University of Malang batch 2018. The sample determination used the Slovin formula and the number of respondents was 75 students. This research uses multiple linear regression model. The results showed that students' perceptions did not have a positive effect on financial accounting courses. Meanwhile, interest has a positive effect on financial accounting courses.Keywords: student perception, student interest and financial accounting.